Global Environmental Threats: why they are hard to see and how a medical model may contribute to their understanding - Chivian, Eric (Cardiovascular Diagnosis and Therapy, 2013)
Our Oxford University Press book, ‘Sustaining Life: How Human Health Depends on Biodiversity’, which was published in 2008, described examples of how our health and lives are affected when we damage the living world (1). I am increasingly alarmed at the current accelerated pace and magnitude of our damaging the global environment, and how little policy-makers and the public seem to recognize this. I am particularly concerned that it is so difficult for most people to grasp what is happening to our small planet, what is happening by our own hands.